Perbedaan Pola Menyusui Bulan Pertama Ibu Melahirkan Seksio Sesarea Dibandingkan Melahirkan Normal di Rumah Sakit Sayang Bayi - Nurmayani, Winda; Julia, Madarina; Prawitasari, Shinta (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: exclusive breastfeeding should be provided until 6 months of age, but the fact proves that the pattern of breastfeeding has decreased. The pattern of the first month lactation is a critical period for the survival of the subsequent breastfeeding, so it is necessary to make efforts to maintain the duration of breastfeeding because the success of the first month breastfeeding will increase mothers’ confidence to continue breastfeeding.Objective: To determine differences in the pattern of the first month breastfeeding in mothers who gave birth by cesarean section compared to those by vaginal delivery in Rumah Sakit Sayang Bayi (Baby Friendly Hospital)Method: Type of research is comparative observational  with a prospective cohort design using a quantitative approach. The research was conducted in Baby Friendly Hospital of RSUD (General Hospital) Mataram City. Total sample 120 consisted of 60 mothers giving birth the caesarean section and 60 mothers vaginal delivery. The independent variable of giving birth by Cesarean Section and vaginal delivery, dependent variable pattern the first month of breastfeeding and external variables age, parity, employment, the incidence of antepartum and postpartum. The sampling technique using consecutive sampling. Analysis of the data used is univaribel, bivariate using Chi-square and Fisher's exact test and multivariable logistic regression and stratification testResult and Discussion: There was no significant correlation between the mode of delivery and the patterns of the first month breastfeeding by including a variable of employment with a value of OR (95% CI) = 1.6 (0.63 to 4.17) and there was a decrease in the value of OR (95% CI ) from 2.5 (1.05 to 5.94) to 1.6 (0.63 to 4.17); there was also no  significant correlation when involving the variable of the incidence of ante partum and post partum with the value of OR (95% CI) = 1.7 (0.45 to 6.26) and OR (95% CI) = 2.3 (0.96 to 5.53), respectively.Conclusion: : There is no difference patterns of breastfeeding mothers first month who gave birth cesarean section compared to normal birth. Caesarean section would affect the pattern of the first month breastfeeding if cesarean section deliveries occurred at housewives and mothers who did not experience the incidence of ante partum. Keywords: pattern of breastfeeding; vaginal deliveries; caesarean section; breast milk;